ROS generating BODIPY loaded nanoparticles for photodynamic eradication of biofilms - Kromer, Charlotte; Schwibbert, Karin; Radunz, Sebastian; Thiele, Dorothea; Laux, Peter; Luch, Andreas; Tschiche, Harald R. (Frontiers in Microbiology, 2023)
Bacterial biofilms can pose a serious health risk to humans and are less susceptible to antibiotics and disinfection than planktonic bacteria. Here, a novel method for biofilm eradication based on antimicrobial photodynamic therapy utilizing a nanoparticle in conjunction with a BODIPY derivative as photosensitizer was developed. Reactive oxygen species are generated upon illumination with visible light and lead to a strong, controllable and persistent eradication of both planktonic bacteria and biofilms. One of the biggest challenges in biofilm eradication is the penetration of the antimicrobial agent into the biofilm and its matrix. A biocompatible hydrophilic nanoparticle was utilized as a delivery system for the hydrophobic BODIPY dye and enabled its accumulation within the biofilm. This key feature of delivering the antimicrobial agent to the site of action where it is activated resulted in effective eradication of all tested biofilms. Here, 3 bacterial species that commonly form clinically relevant pathogenic biofilms were selected: Escherichia coli, Staphylococcus aureus and Streptococcus mutans. The development of this antimicrobial photodynamic therapy tool for biofilm eradication takes a promising step towards new methods for the much needed treatment of pathogenic biofilms.